Immunotolerant p50/NFκB Signaling and Attenuated Hepatic IFNβ Expression Increases Neonatal Sensitivity to Endotoxemia - McKenna, Sarah; Burey, Taylor; Sandoval, Jeryl; Nguyen, Leanna; Castro, Odalis; Gudipati, Suma; Gonzalez, Jazmin; El Kasmi, Karim C.; Wright, Clyde J. (Frontiers in Immunology, 2018)
Sepsis is a major cause of neonatal morbidity and mortality. The current paradigm suggests that neonatal susceptibility to infection is explained by an innate immune response that is functionally immature. Recent studies in adults have questioned a therapeutic role for IFNβ in sepsis; however, the role of IFNβ in mediating neonatal sensitivity to sepsis is unknown. We evaluated the transcriptional regulation and expression of IFNβ in early neonatal (P0) and adult murine models of endotoxemia (IP LPS, 5 mg/kg). We found that hepatic, pulmonary, and serum IFNβ expression was significantly attenuated in endotoxemic neonates when compared to similarly exposed adults. Furthermore, endotoxemia induced hepatic p65/NFκB and IRF3 activation exclusively in adults. In contrast, endotoxemia induced immunotolerant p50/NFκB signaling in neonatal mice without evidence of IRF3 activation. Consistent with impaired IFNβ expression and attenuated circulating serum levels, neonatal pulmonary STAT1 signaling and target gene expression was significantly lower than adult levels. Using multiple in vivo approaches, the source of hepatic IFNβ expression in endotoxemic adult mice was determined to be the hepatic macrophage, and experiments in RAW 264.7 cells confirmed that LPS-induced IFNβ expression was NFκB dependent. Finally, treating neonatal mice with IFNβ 2 h after endotoxemia stimulated pulmonary STAT1 signaling and STAT1 dependent gene expression. Furthermore, IFNβ treatment of endotoxemic neonatal animals resulted in significantly improved survival following exposure to lethal endotoxemia. In conclusion, endotoxemia induced IFNβ expression is attenuated in the early neonatal period, secondary to impaired NFκB-p65/IRF3 signaling. Pre-treatment with IFNβ decreases neonatal sensitivity to endotoxemia. These results support further study of the role of impaired IFNβ expression and neonatal sensitivity to sepsis.